2017
DOI: 10.21919/remef.v12i2.88
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy and Mathematics: A Study among Young Mexican High School Students

Abstract: This work analyzes the influence of mathematical skills on financial literacy among Mexican high school students between 15 and 18 years of age. We use data from a survey constructed explicitly for this purpose, based on measures suggested by Lusardi and Mitchell and the Organisation for Economic Co-operation and Development (OECD). This is the first study of its kind for Mexican youths. Our results confirm that financial literacy levels among Mexican students are low. We offer evidence on the significant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
1
3
0
3
Order By: Relevance
“…En consecuencia, se insiste en colocar la educación financiera con valor curricular en el sector educativo, como un componente fundamental para una ciudadanía que a largo plazo cuente con habilidades financieras para tomar mejores decisiones y obtener mayores beneficios (Huchín y Simón, 2011;Córdova-Rangel et al, 2016;Duque et al, 2016;Denegri et al, 2018). No obstante, este mecanismo presenta retos importantes, pues también se ha de-mostrado que, a pesar de que en los programas educativos se aplican conocimientos financieros con valor curricular, las estadísticas no reflejan resultados positivos (Villagómez e Hidalgo, 2017).…”
Section: Importancia De La Educación Financieraunclassified
“…En consecuencia, se insiste en colocar la educación financiera con valor curricular en el sector educativo, como un componente fundamental para una ciudadanía que a largo plazo cuente con habilidades financieras para tomar mejores decisiones y obtener mayores beneficios (Huchín y Simón, 2011;Córdova-Rangel et al, 2016;Duque et al, 2016;Denegri et al, 2018). No obstante, este mecanismo presenta retos importantes, pues también se ha de-mostrado que, a pesar de que en los programas educativos se aplican conocimientos financieros con valor curricular, las estadísticas no reflejan resultados positivos (Villagómez e Hidalgo, 2017).…”
Section: Importancia De La Educación Financieraunclassified
“…Lo anterior sugiere que esta brecha puede entonces entenderse como consecuencia de las diferencias obtenidas en cuestiones cuantitativas. Reducirla demanda entonces una mayor igualdad en el desarrollo de estas habilidades, así como la atención de otros aspectos no necesariamente cognitivos, por ejemplo, los estereotipos sobre los roles de la mujer y del hombre aprendidos en el hogar (Villagómez e Hidalgo, 2017).…”
Section: Conclusionesunclassified
“…On the other hand, from the educational point of view, the study conducted by Villagómez and Hidalgo (2017) in Mexican high school students, found a positive correlation between the level of mathematical ability and financial literacy. These abilities turn out to be, skills that stimulate logical thinking and the ability to solve problems, positively affecting the ability to plan for the future.…”
Section: Introductionmentioning
confidence: 95%